Time for peace : the essential role of time in conflict and peace processes - Reychler, Luc (Peace and conflict series., 2015)
For building sustainable peace and security, the time is always now. Violence in our world extends beyond armed conflicts: it exists in our social and economic structures, not to mention in our destruction of the environment. How can we build more sustainable development and peace? In this innovative, ambitious book, Dr Luc Reychler argues that we must drastically change our 'temporament', or the way we deal with time. He surveys the vast temporal landscape, and considers its many dimensions, such as how time relates to emotions, religion and conflict, and how our time horizons affect the natu.